Guttae morphology after cultured corneal endothelial cell transplant in Fuchs endothelial corneal dystrophy - Tomioka, Yasufumi; Ueno, Morio; Yamamoto, Akihisa; Numa, Kohsaku; Tanaka, Hiroshi; Kitazawa, Koji; Toda, Munetoyo; Koizumi, Noriko; Tanaka, Motomu; Hamuro, Junji; Sotozono, Chie; Kinoshita, Shigeru (JAMA ophthalmology, 2024)
Whether guttae in Fuchs endothelial corneal dystrophy (FECD) can be removed by polishing without Descemet stripping and whether postoperative maintenance of reduced guttae can be achieved through cultured corneal endothelial cell (CEC) transplant therapy are critical issues to be addressed.To investigate the decrease of guttae through polishing degenerated CECs and abnormal extracellular matrix (ECM) without Descemet stripping and to observe the behavior of guttae following cultured CEC transplant.This case series prospective observational study was conducted in a hospital outpatient clinic setting. Between December 2013 and January 2019, 22 eyes with corneal endothelial failure caused by FECD received cultured CEC transplant therapy at Kyoto Prefectural University Hospital. Of these, 15 eyes were consistently monitored at the same central corneal area during the preoperative phase, as well as in the early (within 1 year) and late (after 3 years) postoperative phases. The images from these phases were categorized into 3 groups: typical guttae, atypical guttae, and no guttae.Cultured CEC transplant therapy.Proportion of guttae in the observable area was measured, comparing the early and late postoperative phases for each group.The mean age of the patients at the time of surgery was 69 years (range, 49-79 years). All 15 eyes exhibited the presence of confluent guttae preoperatively (100%). Among these, 3 of 15 eyes belonged to male patients. The early postoperative phase of guttae morphologies was classified into 3 groups: 5 eyes with typical guttae, 7 with atypical guttae, and 3 with no guttae. The decrease in the number of these guttae was achieved by surgical procedures. The median percentage of guttae in the typical guttae, atypical guttae, and no guttae groups was 41.8%, 44.4%, and 16.2%, respectively, in the early phase, and 42.2%, 38.2%, and 18.8%, respectively, in the late phase.The findings demonstrate that in some cases of FECD, guttae can be removed by scraping and polishing abnormal ECM and degenerated CECs, while preserving the Descemet membrane. Furthermore, cultured CEC transplant resulted in no increase in guttae for up to 3 years, providing insights into surgically eliminating guttae.
Gesehen am 15.01.2025